2012
DOI: 10.1007/s10546-012-9790-x
|View full text |Cite
|
Sign up to set email alerts
|

Length-Scale Similarity of Turbulent Organized Structures over Surfaces with Different Roughness Types

Abstract: We examine the similarity of turbulent organized structures over smooth and very rough wall flows. Turbulent flow fields in horizontal cross-sections were measured using particle image velocimetry, and the characteristics of turbulent organized structures over four types of surfaces were investigated. Measurements were conducted at several measurement heights across the internal boundary layer. The length and width of turbulence structures were quantified using a two-point correlation method. We selected two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
18
2
Order By: Relevance
“…Nevertheless, the present results agree with those of Volino et al [35] who found that the length scales of the 2D roughness case were significantly higher than the 3D case throughout the height of the boundary layer. Conversely, the present results and those of Volino et al [35] are contradicted by Takimoto et al [34] whose results show that 3D configurations result in larger L u than those of 2D configurations with equal AR. This discrepancy may be a result of the simulation method leading to a smaller boundary layer to building height ratio as no spires were used by Takimoto et al [34] to produce turbulence and it is clear that L u tapers off to very small values with increasing height in their work.…”
Section: Streamwise Integral Length Scalecontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the present results agree with those of Volino et al [35] who found that the length scales of the 2D roughness case were significantly higher than the 3D case throughout the height of the boundary layer. Conversely, the present results and those of Volino et al [35] are contradicted by Takimoto et al [34] whose results show that 3D configurations result in larger L u than those of 2D configurations with equal AR. This discrepancy may be a result of the simulation method leading to a smaller boundary layer to building height ratio as no spires were used by Takimoto et al [34] to produce turbulence and it is clear that L u tapers off to very small values with increasing height in their work.…”
Section: Streamwise Integral Length Scalecontrasting
confidence: 99%
“…Conversely, the present results and those of Volino et al [35] are contradicted by Takimoto et al [34] whose results show that 3D configurations result in larger L u than those of 2D configurations with equal AR. This discrepancy may be a result of the simulation method leading to a smaller boundary layer to building height ratio as no spires were used by Takimoto et al [34] to produce turbulence and it is clear that L u tapers off to very small values with increasing height in their work. All results seem to approach a similar value as z/h approaches unity except the 2D configuration of Volino et al [35] with a high AR.…”
Section: Streamwise Integral Length Scalecontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore the estimate of the Eulerian integral length scales is generally calculated as the distance at which the correlation function falls below a threshold value. For example Bewley et al (2012) assumed a value of 0.5 whereas Takimoto et al (2013) adopted 0.4. Note that this method may be problematic when computing scales associated to the ρ uu functions, since the extent of the iso-correlation lines corresponding to the threshold value may not be fully captured by the PIV field (see Fig.…”
Section: Integral Length and Time Scalesmentioning
confidence: 99%
“…The near-surface velocity gradient ∂ u /∂z| z/δ=0 over different rough surfaces shows a similar behavior, i.e., velocity increases more sharply with increasing aerodynamic resistance, signifying the elevated drag in the near-surface region (Figure 2). The length scales of flows are highly correlated with the velocity gradient at different elevation [54].…”
Section: Friction Velocitymentioning
confidence: 99%